Maintenance of Lampung Language in Padang Cermin District - Citra Wulandari (TEKNOSASTIK, 2018)
The aim of this study is to know how far the maintenance and the shift of Lampung language in Padang Cermin district are. Most of Padang Cermin society uses their mother tongue which is Lampung language while their second language is Indonesia Language. Most of them establish the kinship or directly interact with Lampung ethnic so that they can speak Lampung language. A qualitative method was applied in this study and involves 30 respondents from five villages in Padang Cermin district which are Tanjung Mas, Paya, Sanggi, Pal Satu, and Durian based on gender, ages, marriage status, education, occupation and place of birth by observing, interviewing and giving questionnaire. The result shows that there are still many of them uses the dominant language which is Lampung language and the language attitudes towards them tend to be positive. It also found that the language shift occurs from several factors; education development, social, government, behavior, and economic development.Key Words: Language attitude, language maintenance, language shift, Padang Cermin